Analysis of Women's Contribution to White Coffee Income in Suco Manelima, Laklubar Administrative Post, Manatuto Municipality - Heribertos A. Colo; Andre do Carmo; Eva de Almeida (Jurnal Syntax Transformation, 2025)
This study aims to analyze the income of Suco Manelima white coffee farmers in Laclubar, Manatuto Municipality, as well as the contribution of women in increasing family income. Agriculture, particularly coffee, is a vital sector for Timor Leste's economy. The research was conducted from March 4 to April 4, 2019, using primary and secondary data collection methods. Primary data were obtained through direct interviews and questionnaires, while secondary data were obtained from relevant sources. The findings show that the total income of white coffee farmers reached U$ 29,650, of which women's contribution in increasing family income was 61%. Total family income was recorded at U$ 18,800, which shows the significant role of women in the household economy. The results confirm that women play an important role in increasing family income through the coffee farming sector. Despite technological limitations and challenges in production, women's contribution in the production process has a positive impact on the family economy and the community. This research highlights the importance of women's empowerment in the agricultural sector to improve the family economy in Timor Leste. Sustainable agricultural development and increased access to technology are key to advancing the sector and reducing poverty.